SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN LOKASI PETERNAKAN AYAM BROILER DENGAN METODE PERBANDINGAN EKSPONENSIAL DAN NAIVE BAYES - Ari Wibowo; Anton Setiawan Honggowibowo (Institut Teknologi Dirgantara Adisutjipto, 2014)
Location is an important role in the success of building a broiler chicken farm. Fault location can be fatal in business continuity. Decision support system is very useful to help help determine the location of broiler chicken farms right. By using the decision support system will give results in the form of value that can be used as a comparison to any alternative location. The method used is Metode Perbandingan Eksponensial (MPE) and Naive Bayes. By using both methods can provide clearer results. Metode Perbandingan Eksponensial is better than the Naive Bayes method, this is because the value generated by the Metode Perbandingan Eksponensial has a contrasting difference in each outcome so as to reduce the refraction that may occur.